Peculiarities of the colon microflora condition in pregnant women with asymptomatic bacteriuria - Rynzhuk, Larisa Vasylivna; Rynzhuk, Vasyl Yefremovych; Gresko, Marina Dmitrуina; Bulik, Tatyana Sergуivna; Sheremet, Anastsia Mihaylivna (Journal of Education, Health and Sport, 2018)
The investigation deals with studying of species content and population level of the colon microflora in pregnant women with asymptomatic bacteriuria in comparison with practically healthy pregnant women. A significant disorder of the qualitative and quantitative composition of the colon microflora content has been found to occur in pregnant women with asymptomatic bacteriuria, which in combination with physiological factors associated with pregnancy may result in the development of asymptomatic bacteriuria.